Use of Accurate V3 software as an introduction to accounting skills in “Merdeka Belajar Kampus Merdeka” Program - Retna Safriliana; Diyah Sukanti Cahyaningsih; Parawiyati Parawiyati (Jurnal Penelitian, 2021)
In supporting the student exchange program at the national Program "Merdeka Belajar Kampus Merdeka" (MBKM), the department needs to prepare courses that can be superior to be offered to students. In the Accounting Department University of Merdeka Malang, there are accounting practicum courses. This course provides students with skills in utilizing accounting software. This study wants to see the technology acceptance model for using Accurate Accounting V3 software for cross-departmental students who are the object of research in an experimental class. Data was obtained by distributing questionnaires to class participants who had completed the practicum. By using path analysis, the results show that perceived usefulness and perceived convenience affect user behavior interest. Perceived usefulness and interest in user behavior affect software to use, while perceived ease of use does not affect software usage decisions. Interest in user behavior is proven as an intervening variable on the effect of perceived usefulness on the use of the software.